How Flipped Classroom Helps the Learning in the Times of Covid-19 Era? - Anugrah Anugrah; Nurdin Ibrahim; Moch. Sukardjo (JTP - Jurnal Teknologi Pendidikan, 2020)
In 2020, online learning rapidly grows due to the pandemic of COVID-19 that affected the changes in global conditions. All learners and educators have to be ready for online learning. This research was aimed to explore the implementation of the flipped classroom during the Covid-19 pandemic outbreak in 2020. This research setting was at Universitas Negeri Jakarta, one of the campuses that eliminated campus activities due to the high Covid-19 spread in Jakarta. Referring to the learning standards of AECT, the researchers used qualitative descriptive methods. The techniques of collecting data were observation, interviews, and questionnaires to all students who took E-Learning Design courses at the Master of Educational Technology, Postgraduate Program, Universitas Negeri Jakarta. The research results proved that learning during the Covid-19 pandemic using flipped classrooms in the E-Learning Design course has met ten online learning standards by AECT and provides satisfaction for students and lecturers. In addition, according to research results, the use of technology does not need to be grandiose. Accordingly, it should optimize the platform often used on daily basis to utilize the flipped classroom.